Light-induced olefin metathesis - Vidavsky, Yuval; Lemcoff, N. Gabriel (Beilstein Journal of Organic Chemistry, 2010)
Light activation is a most desirable property for catalysis control. Among the many catalytic processes that may be activated by light, olefin metathesis stands out as both academically motivating and practically useful. Starting from early tungsten heterogeneous photoinitiated metathesis, up to modern ruthenium methods based on complex photoisomerisation or indirect photoactivation, this survey of the relevant literature summarises past and present developments in the use of light to expedite olefin ring-closing, ring-opening polymerisation and cross-metathesis reactions.
Keywords: catalysis; light activation; olefin metathesis; photoactivation; photoinitiation; photoisomerisation; RCM; ROMP; ruthenium; tungsten